Philip's city: from Bethsaida to Julias - Strickert, Frederick M. (Liturgical Press, 2011)
Sources -- The Iron Age city of Tzer -- Resettlement in the Hellenistic age -- Home of the apostles -- Across the sea-- to Bethsaida -- Fishing village -- Farming and flax production -- Houses of fishermen and others -- Jews and gentiles in Bethsaida -- Philip as ruler -- Philip's marriage -- The founding of Bethsaida as Julias -- The multiplication of loaves and fishes -- The healing of the blind man -- Woe saying against Bethsaida -- The early church, a communal meal, and the sayings of Jesus -- John 12:24 and Livia Karpophoros -- The destruction of Bethsaida